Whole transcriptome sequencing reveals biologically significant RNA markers and related regulating biological pathways in cardiomyocyte hypertrophy induced by high glucose. Issue 1 (22nd September 2018) - Meng, Zheying; Chen, Cui; Cao, Hongli; Wang, Jingyi; Shen, E
Abstract: Cardiomyocyte hypertrophy is a physiological adaptation used in an attempt to augment or preserve cardiac function for short periods. Long‐term cardiomyocyte hypertrophy often progresses to heart failure. Previous studies have presented comprehensive mechanisms underlying cardiomyocyte hypertrophy, such as signaling pathways, marker genes, and marker miRNAs or lncRNAs. However, the mechanism in RNA level is still unclear. In this study, we used the whole transcriptome technology on cardiomyocety hypertrophy cells, which were cultured with a high concentration of d ‐glucose. Many differentially expressed markers, including genes, lncRNAs, miRNAs, and circRNAs were identified. Further quantitative real‐time PCR verified the highly specific expressed genes, such as Eid1, Timm8b, Mrpl50, Dusp18, Abrc1, Klf13, and Igf1. Moreover, the functional pathways were also enriched with the differentially expressed lncRNA, miRNA, and circRNA. Our study gives new insights into cardiomyocyte hypertrophy and makes great progress in comprehending its mechanism. Abstract : Our study gives new insights into cardiomyocyte hypertrophy and makes a great progress in comprehending its mechanism.